2003
DOI: 10.1021/es0205838
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Three Techniques Used To Measure Diffusive Gas Exchange from Sheltered Aquatic Surfaces

Abstract: Three approaches commonly used to quantify diffusive gas exchange across aquatic surfaces were compared in a densely treed, low-wind environment Diffusive surface fluxes of carbon dioxide (CO2) and methane (CH4) from a small boreal reservoir were estimated using (i) surface water concentrations, the thin boundary layer (TBL) equation, and gas transfer velocities (k) calculated using sulfur hexafluoride (SF6); (ii) surface water concentrations, the TBL equation, and k estimated from wind speed; and (iii) static… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
134
4
9

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(157 citation statements)
references
References 44 publications
10
134
4
9
Order By: Relevance
“…The overall trend toward FC overestimations in our study is still consistent with the conclusions of Matthews et al (2003). Their FC overestimations were much more important in calm-water conditions than they were when waves were present at higher wind speeds.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The overall trend toward FC overestimations in our study is still consistent with the conclusions of Matthews et al (2003). Their FC overestimations were much more important in calm-water conditions than they were when waves were present at higher wind speeds.…”
Section: Discussionsupporting
confidence: 91%
“…Bias and corrections for FC measurements-Our FC evaluation agrees with those of many other studies that found that fluxes are overestimated when measured by FC methods by perturbing the air-water interface (Kremer et al 2003;Matthews et al 2003;Lambert and Fréchette 2005). Tokoro et al (2008) also measured turbulence inside and outside their FC, but they did not find major disagreements between the two types of measurements.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Caveats to C flux estimates-A variety of methods are available to estimate CO 2 flux from lakes, each with its relative merits (Anderson et al 1999;Matthews et al 2003;Soumis et al 2008). In this study, gas flux estimates were derived from well-established boundary-layer equations (Cole and Caraco 1998) and observed wind speed but did not account for the effects of precipitation or convective mixing (Anderson et al 1999;Eugster et al 2003).…”
Section: Discussionmentioning
confidence: 99%